2021
DOI: 10.1039/d1cc03589d
|View full text |Cite
|
Sign up to set email alerts
|

Highly regioselective and stereoselective synthesis of C-Aryl glycosides via nickel-catalyzed ortho-C–H glycosylation of 8-aminoquinoline benzamides

Abstract: C-Aryl glycosides are of high value as drug candidates. Here a novel and cost-effective nickel catalyzed ortho-CAr-H glycosylation reaction with high regioselectivity and excellent α-selectivity is described. This method shows...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Hosted file image18.emf available at https://authorea.com/users/596681/articles/630065-c-glycosidesynthesis-enabled-by-nickle-catalysis Scheme 17 Nickel-catalyzed mannosylation of peptides in aqueous media and its plausible mechanism Hosted file image19.emf available at https://authorea.com/users/596681/articles/630065-c-glycosidesynthesis-enabled-by-nickle-catalysis Later, Liang and co-workers developed a regioselective and stereoselective method for the preparation of aryl C-glycosides through nickel-catalyzed ortho -C-H glycosylation of 8-aminoquinoline benzamides (Scheme 18). [27] The reaction exhibits excellent α-selectivity and regioselectivity. Notably, the scope of glycosyl bromide is somewhat limited.…”
Section: Scheme 16 Nickel-catalyzed Synthesis Of C-mannosylated Glyco...mentioning
confidence: 97%
“…Hosted file image18.emf available at https://authorea.com/users/596681/articles/630065-c-glycosidesynthesis-enabled-by-nickle-catalysis Scheme 17 Nickel-catalyzed mannosylation of peptides in aqueous media and its plausible mechanism Hosted file image19.emf available at https://authorea.com/users/596681/articles/630065-c-glycosidesynthesis-enabled-by-nickle-catalysis Later, Liang and co-workers developed a regioselective and stereoselective method for the preparation of aryl C-glycosides through nickel-catalyzed ortho -C-H glycosylation of 8-aminoquinoline benzamides (Scheme 18). [27] The reaction exhibits excellent α-selectivity and regioselectivity. Notably, the scope of glycosyl bromide is somewhat limited.…”
Section: Scheme 16 Nickel-catalyzed Synthesis Of C-mannosylated Glyco...mentioning
confidence: 97%
“…Then, Liu and co-workers reported the similar Ni(0)-catalyzed asymmetric reductive cyclization of intramolecular O -carbonyl-alkynes with better substrate scope when using ( S , S )-DI-BIDIME L3 instead of ( S )-AntPhos L1 as a chiral ligand (Scheme 5). 19 This new ligand was first reported in 2018 by Tang et al 20 and features two key advantages: (1) DI-BIDIME lacks hydrogen at the 7-position, which not only prevents the potential C–H functionalization at the 7-position, 21 but also avoids cleavage of the adjacent C–O bond in the presence of metallic nickel; 22 (2) the two phosphorus atoms in DI-BIDIME can function independently by reducing the ligand entropy by half. This could effectively increase the longevity of the catalyst.…”
Section: Nickel-catalyzed Asymmetric Cyclization Of Carbonyl-alkynesmentioning
confidence: 99%
“…The product was isolated in 45% yield (63.7 mg). 1 9, 159.3, 149.3, 138.7, 138.6, 138.54, 138.48, 138.4, 135.9, 131.7, 128.5, 128.4, 128.2, 127.84, 127.80, 127.76, 127.53, 127.46, 125.0, 121.4, 113.8, 112.7, 77.8, 76.6, 75.3, 75.2, 73.4, 72.8, 72.4, 72.0, 69.2, 68.8, 55.5 (8). Colorless syrup, R f = 0.4, hexane:ethyl acetate = 3:1 (v/v).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Over the past few years, metal-catalyzed C – H glycosylation reactions have emerged as a new strategy for the synthesis of C -glycosides, enabling more streamlined retrosynthetic disconnections. In the previous studies, we and others showed that amide-linked bidentate auxiliaries can direct C – H glycosylation with glycosyl chloride donors under palladium catalysis . Liang recently reported that the aminoquinoline auxiliary can facilitate ortho C – H glycosylation of arenes with chloride donors using nickel catalysts (Scheme B) . Herein, we report a ruthenium-catalyzed C – H glycosylation of arenes with chloride donors using a monodentate pyridine directing group (Scheme C).…”
mentioning
confidence: 99%
See 1 more Smart Citation